Development of KASP markers assisted with soybean drought tolerance in the germination stage based on GWAS - Jia, Qianru; Zhou, Miaomiao; Xiong, Yawen; Wang, Junyan; Xu, Donghe; Zhang, Hongmei; Liu, Xiaoqing; Zhang, Wei; Wang, Qiong; Sun, Xin; Chen, Huatao (Frontiers in Plant Science, 2024)
Soybean [Glycine max (L.)Merr.] is a leading oil-bearing crop and cultivated globally over a vast scale. The agricultural landscape in China faces a formidable challenge with drought significantly impacting soybean production. In this study, we treated a natural population of 264 Chinese soybean accessions using PEG-6000 and screened 17 strong drought-tolerant soybean germplasm in the germination stage. Leveraging 2,597,425 high-density SNP markers, we conducted Genome-Wide Association Studies (GWAS) and identified SNPs and candidate genes significantly associated with drought tolerance. Furthermore, we developed two KASP markers closely linked to drought tolerance.